IoT security risk analysis - Sakib, Nazmus; Jerin, Ismot; Khan, Nuzhat; Quader, Shaela (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2017.